(3GdJaSjQGJ heWGQM GdTYGYGJs - (3CHh eQhGf GdGSJLjs ((3eMeO Hf Ydi GdHbGQ s)
(3ChdgG (B:s
(3CWGd Gddg HbGA GdhRjQ GdLdjd GdbGVi CHj GdbGSe SjOi , hCYdi YOOi hRGOg HSWI ai GdfHGgI hGdage hHYO ajYde Gddg JHGQc GSeg aEfi CQOJ Gf Cbje GdeNGWHI ebGe GdecGdeI s
(3BNQgG (B:s
(3hLedI GdCeQ aEfg dGjfHZi dCMO Gf jSjQ HgPG GdJaSjQ Edi HYO JUMjM OQLI GdWGdY HGdfi hOGQjf GdePchQjf hfSCd ef HjOg GdNjQ hGdaVd Cf jRjOfG hEjGc ef CaVGdg cedJ QSGdI CHj eQhGf GdESJLi s
(3Vef eLehY , JQJjHgG (B: (3ef U (B10 - (3U(B16s
(3HgG fXGe GdJYbjHIs
(3cJHJ HQSe eMeO Hf Ydi Hf EOQjS Gdcheis
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B2 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdESchQjGd (B(939/2) s
Keywords: (3Gdadcs